Cultural Influences on the Interpretation of Hadith: A Comparative Study of Syuhudi Ismail, Ibn Taymiyyah, and Muhammad Ibn Abd Al-Wahhab - Badar Alam Kalasuba; Mochammad Qosim; Lukman Hakim; Mohammad Hamsa Fauriz (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
The Prophetic hadith is one of the main sources of Islamic teachings after the Qur'an. However, the understanding and application of hadith is not always uniform in different places and times. One of the factors that influence the interpretation of hadith is the cultural background of the scholars who study them. This study discusses how the cultural background influenced the thinking of Ibn Taymiyyah and Muhammad bin Abdul Wahhab so that they rejected culture as part of Islamic teachings, as well as how Syuhudi Ismail's cultural background shaped his views which are more flexible in accepting culture as part of the practice of the Prophet's hadith. Using historical and comparative analysis methods, this study found that Ibn Taymiyyah and Muhammad bin Abdul Wahhab were born in a social context that tended to be puritanical and tried to maintain the purity of Islamic teachings from external influences, so they were stricter in understanding hadith within the limits of the original text and context. In contrast, Syuhudi Ismail, who lives in a plural and culturally inclusive society, tends to interpret hadith with an interdisciplinary approach that considers cultural relevance. Thus, this study confirms that culture has a significant role in shaping the understanding of hadith and its application in the lives of Muslims.